CHANGE IN THE DISSOLUTION RATES OF ALKALI FELDSPARS AS A RESULT OF SECONDARY MINERAL PRECIPITATION AND APPROACH TO EQUILIBRIUM - Alekseyev V.A.; Medvedeva L.S.; Prisyagina N.I.; Meshalkin S.S.; Balabin A.I. (My University, 1997)
Reaction rates of congruent and incongruent dissolution of sanidine in NaHCO3 solution (0.1 m) and albite in KHCO3 solution (0.1 m) as well as the reaction rates of precipitation of secondary minerals (analcime and sanidine) have been measured at 300°C, 88 bars, and pH 9. At congruent stage, the reaction rates change, as equilibrium is approached, according to the following law: where k is the rate constant, S is the surface area of the mineral, Q is the activity quotient, K is the equilibrium constant, and p and q are fitted parameters. For dissolution of sanidine and albite, the values of k (mol/m2/sec), p, q are equal to 5.0 · 10−7, 0.16, 1.4, and 4.5 · 10−7, 0.76, 90, respectively. Strong correlation between p and q has been revealed allowing us to reduce the number of fitted parameters. Deviation of p and q from unity suggests a complex dissolution mechanism involving crystal defects and/or a number of paralle and successive elementary reactions with comparable rates.Incongruent dissolution of the primary minerals is controlled by precipitation reactions of secondary ones. Precipitation rates may also obey the rate law given above, but determination of coefficients in this case was difficult due to change of S in processes of nucleation, growth, coalescence of crystals, and formation of pores filled with primary minerals. Correlation between reaction rates of primary mineral dissolution and secondary mineral precipitation is more rigid than one might expect from simultaneous solution of two rate equations. Under conditions of low kinetic activity of the surface, this rigid correlation can be explained, by analogy with electrode processes, using a source-sink mechanism. The experimental data obtained for the most widespread and typical rock-forming minerals are of major importance to improving kinetic models of water-rock interaction.